WORKING AND NON-WORKING STATUS OF UNDERGRADUATE STUDENTS' LANGUAGE LEARNING STRATEGIES - Asti Gumartifa; Indawan Syahri (IKIP Siliwangi, 2022)
Study while working has several effects in advanced higher education. Working and studying at the same time in university can be as reward and stressful. Thus, language learning strategies for working students and non-working students play an important role in the effectiveness and efficiency of English language learning. The researchers examined whether or not there is significant differences of English language learning strategies used by working and non-working students. Quantitative descriptive study was used to describe the findings. The result showed that working students applied memory strategies dominantly. The number average mean score of memory strategy was 4.02 in the category of high, where compensation learning strategies was 2.77 that categorized the lowest mean average. Non-working students applied all learning strategies at the medium level category. The highest number of mean average of language learning strategies was cognitive strategies with the average mean was 3.11. Total number mean average of metacognitive and affective strategies was the same 2.79. Compensation, memory, and social strategy were also in the medium category with different total numbers average. The mean average of compensation strategies was 3.01, memory strategy was 2.93, and social strategy was 2.75. Keywords: English Language, Learning Strategy, Status, Category, Undergraduate